2016
DOI: 10.3141/2583-04
|View full text |Cite
|
Sign up to set email alerts
|

Safety Evaluation of Seven of the Earliest Diverging Diamond Interchanges Installed in the United States

Abstract: Diverging diamond interchanges (DDIs) are increasingly popular because they provide improved traffic operations and cost savings. On the basis of theory, DDIs should be safer than conventional diamonds, but previous empirical safety studies have been limited. The objectives of this work were, therefore, to conduct a broader safety evaluation of DDIs and to recommend a crash modification factor (CMF) for the conversion of a conventional diamond to a DDI. The team analyzed seven of the earliest DDIs in the Unite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 1 publication
1
18
0
Order By: Relevance
“…The crash reductions reported through use of the empirical Bayes (EB) method were 62.6% for fatal and injury (FI) crashes, 35.1% for property damage only (PDO) crashes, and 47.9% for total crashes (6). Similar results were reported later in a national study conducted by Hummer et al, which included DDI sites in Missouri, Kentucky, New York, and Tennessee (7). They reported that the DDI design effected a 33% reduction in total crashes and a 41% reduction in FI crashes.…”
supporting
confidence: 62%
“…The crash reductions reported through use of the empirical Bayes (EB) method were 62.6% for fatal and injury (FI) crashes, 35.1% for property damage only (PDO) crashes, and 47.9% for total crashes (6). Similar results were reported later in a national study conducted by Hummer et al, which included DDI sites in Missouri, Kentucky, New York, and Tennessee (7). They reported that the DDI design effected a 33% reduction in total crashes and a 41% reduction in FI crashes.…”
supporting
confidence: 62%
“…In the present study, a 60 s cycle length was found as the A lower delay period will not only save the user time and associated fuel cost (i.e., socio-economic benefits), it will also reduce the vehicular emissions (i.e., environmental impact), particularly carbon monoxide (CO) and hydrocarbons (HC), which are produced at a much higher rate during idling in comparison to the cruising condition [31]. Past studies compared the pre-and post-installation conditions for DDI at seven locations in the USA based on several years of traffic data analysis [32,33]. The main findings were, (i) a 33% reduction in the number of crashes for DDI, and (ii) around 60% reduction in the severity of the crashes, i.e., injuries and fatalities.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Several researchers have studied and evaluated the effectiveness of DDI's on safety while taking crash data of existing DDI's into consideration [4][5] [6]. Safety evaluation methods, including the Comparison Group Method and the Empirical Bayes Method, among others, have been applied to compare and evaluate DDI safety improvements.…”
Section: A Safety Evaluationmentioning
confidence: 99%
“…Several studies have researched driver behavior in DDIs, one of which was done by Joe Bared [4]. He explains that some drivers may still be confused about DDIs because they are unfamiliar with this new design.…”
Section: Main Goals For the Ddimentioning
confidence: 99%